1996
DOI: 10.1002/(sici)1097-0215(19960822)69:4<329::aid-ijc16>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the tumour markers CA 125 II and CA 72-4 in ovarian carcinoma

Abstract: In a retrospective study we compared the usefulness of the tumour marker CA 72-4 with the established marker CA 125 II (both EIA on Cobas-Core, Hoffmann LaRoche, Basel Switzerland) at the time of primary diagnosis of ovarian carcinoma (n = 123) in order to discriminate between ovarian carcinomas of different histological type. We compared their diagnostic value, behaviour in follow-up care and evaluated possible combinations. Fixing specificity at 95% vs. benign gynaecological diseases (n = 37) as the clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 12 publications
3
23
0
1
Order By: Relevance
“…Several studies have shown that CA125 is the marker of first choice for diagnosis of ovarian cancer (2,9,(12)(13)(14)(15)(16)(17). However, specificity of CA125 is limited by various benign diseases, particularly those affecting the visceral epithelia, e.g., when pleural, pericardial or peritoneal effusions are present (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that CA125 is the marker of first choice for diagnosis of ovarian cancer (2,9,(12)(13)(14)(15)(16)(17). However, specificity of CA125 is limited by various benign diseases, particularly those affecting the visceral epithelia, e.g., when pleural, pericardial or peritoneal effusions are present (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative sensitivity and specificity could be improved by combination with other cancer antigens, such as CA15-3 and CA72-4 (14,16). Further, prognostic value of CA125 values was found (18,19).…”
Section: Bereitgestellt Von | Universitaetsbibliothek Der Lmu Muenchenmentioning
confidence: 96%
See 1 more Smart Citation
“…However, malignant transformation usually alters this. [131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146] Alterations in expression of mucin carbohydrate or peptide antigens or both are progressively described in carcinomas developed from various tissues such as breast, [147,148] endometrium, [149] ovary, [150,151] pharynx and larynx, [152] lung, [153] stomach, [154,155] liver, [156] gall bladder, [157,158] pancreas, [159,160] and small and large intestine. [161][162][163] Some mucins are rarely expressed in normal tissues, but are anomalously expressed in tumoural tissues.…”
Section: Mucins and Tumoursmentioning
confidence: 99%
“…This confirms previous reports that showed CA72-4 as the predominant mucinous marker, whereas CA125 predominated with nonmucinous disese. 41,42 A total of 7 of the 30 patients with cancer were diagnosed at stage I or stage II. When the data were evaluated based on disease stage at diagnosis, CA125 was only elevated for 2 of these cases, whereas CA72-4 was elevated in 5 of the cases.…”
Section: Ca72-4mentioning
confidence: 99%